ANTIBACTERIAL AND ANTIOXIDANT ACTIVITY OF A CHEMICALLY INDUCED MUTANT OF XANTHORIAPARIETINA - S. Ali; H. N. Hameed (Journal of Animal and Plant Sciences, 2019)
Biological active secondary metabolite parietin was extracted from wild-type and mutant strain of lichen Xanthoriaparietina. Six different solvents (acetone, ethanol, methanol, hexane, chloroform and distilled water) were used to extract parietin. The parietin activity was found to be maximum when extraction was carried out with 3 ml of methanol at 30ºC for 1h. The extracts were proceeded to antibacterial activity against different strains of bacteria.Anion DPPH (1,1-Diphenyl-2-picrylhydrazyl) scavenging, reducing power and total flavonoid content were used to analyze the antioxidant activity. HPLC analysis represented more than 90% purity of methanol extract with some trace elements. The antioxidant activity increased with increasing concentration of methanol extract. EMS treated strain represented maximum DPPH scavenging activity i.e., 84±3.36% which was 2.08 fold higher than the wild-type. Maximum reduction potential was found to be 0.237±0.0118 which was 1.83 fold higher than wild-type. Mutagen concentration of 0.5 mM exhibited strong parietin activity. The extracts of EMS treated mutant variant revealed strong antimicrobial activity (22 mm for bacteria) as compared to the wild-type and MMS treated variant. It was concluded that by increasing mutagen exposure time, the parietin activity decreased in terms of its antimicrobial activity.
Keywords: Xanthoriaparietina; parietin; chemical mutagen; antioxidant; antimicrobial; secondary metabolite